2016
DOI: 10.3329/sja.v14i1.29577
|View full text |Cite
|
Sign up to set email alerts
|

Crop productivity and nutrient uptake of fenugreek (Trigonella foenum-graecum L.) as influenced by integrated nutrient management

Abstract: A field experiment was carried out at Spices Research Centre, Shibgonj, Bogra during two consecutive years, 2013-2014 and 2014-2015 to evaluate the response of integrated nutrient management on nutrient uptake, protein content and seed yield of fenugreek (Trigonella foenumgraecum L.) var. BARI Fenugreek-2. The field experiment was conducted in combination with inorganic fertilizer and organic manure. The result showed that the treatment T 7 compeises application of PM @ 4 t ha -1 + CF (IPNS) produced the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…In this study, greater biomass and greater yield were observed in the P 0 U 180 and P 68 U 112 treatments compared with the unfertilized control. Consistent with previous studies (Moe, Mg, Win, & Yamakawa, 2017;Naher, Fahim, & Wadud, 2016), these results indicate that a combination of PL and fertilizer N or fertilizer N alone can increase total N uptake. These results also indicate that applying PL alone to winter canola in the short term may not satisfy plant N requirements due to the slow mineralization of litter N, whereas a combination of PL and fertilizer N could supply sufficient N as well as other nutrients needed to optimize canola production.…”
Section: Nitrogen Concentration and Uptakesupporting
confidence: 92%
“…In this study, greater biomass and greater yield were observed in the P 0 U 180 and P 68 U 112 treatments compared with the unfertilized control. Consistent with previous studies (Moe, Mg, Win, & Yamakawa, 2017;Naher, Fahim, & Wadud, 2016), these results indicate that a combination of PL and fertilizer N or fertilizer N alone can increase total N uptake. These results also indicate that applying PL alone to winter canola in the short term may not satisfy plant N requirements due to the slow mineralization of litter N, whereas a combination of PL and fertilizer N could supply sufficient N as well as other nutrients needed to optimize canola production.…”
Section: Nitrogen Concentration and Uptakesupporting
confidence: 92%
“…Significantly, highest N P K use efficiency was obtained with 100 % RDF 3.18, 7.90 and 15.81 kg kg -1 . Similar results have also been reported by Naher et al [8] in fenugreek, Javiya et al [9] in coriander, Mevada et al [10] and Kalasare et al [11] in fennel [12][13].…”
Section: Effect Of Nutrient Managementsupporting
confidence: 89%
“…The findings of this study were similar to other studies reported earlier. Islam et al 30 and Naher et al 31 reported that the CM contained N: 1.6%-1.9%; P: 1.5%-1.6%; K: 0.85%-1.7%; and S: 0.71%-1.6%, respectively.…”
Section: Feedstock Composition Of Manure From Chicken Fed With Differ...mentioning
confidence: 98%